CONTROVERSIAL ISSUES OF CHOOSING A METHOD OF TREATMENT OF ACUTE LUNG ABSCESSES IN PATIENTS WITH DIABETES MELLITUS - Khamdamov, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Methods of treating acute lung abscesses in many respects, despite their long history of solving the problem, are still far from perfect. Naturally, as in the case of any surgical infection, the discovery of antibiotics has made it possible to reconsider many aspects of treatment tactics, giving preference to the latter. However, it's not that simple here. In this review article, we tried to select relevant modern literature on controversial issues of methods for treating acute lung abscesses in diabetes mellitus. We conducted a critical analysis and summed up the relevant results of our research. We will be grateful if readers pay attention to provide their feedback on our work.